Sequential sulfur-based denitrification/denitritation and nanofiltration processes for drinking water treatment - Asik, Gulfem; Yilmaz, Tulay; Di Capua, Francesco; Uçar, Deniz; Esposito, Giovanni; Sahinkaya, Erkan (Academic Press, 2021)
Efficient and cost-effective solutions for nitrogen removal are necessary to ensure the availability of safe drinking water. This study proposes a combined treatment for nitrogen-contaminated groundwater by sequential autotrophic nitrogen removal in a sulfur-packed bed reactor (SPBR) and excess sulfate rejection via nanofiltration (NF). Autotrophic nitrogen removal in the SPBR was investigated under both denitrification and denitritation conditions under different NO3− and NO2− loading rates (LRs) and feeding strategies (NO3− only, NO2− only, or both NO3− and NO2− in the feed). Batch activity tests were carried out during SPBR operation to evaluate the effect of different feeding conditions on nitrogen removal activity by the SPBR biofilm. Bacteria responsible for nitrogen removal in the bioreactor were identified via Illumina sequencing. Dead-end filtration tests were performed with NF membranes to investigate the elimination of excess sulfate from the SPBR effluent. This study demonstrates that the combined process results in effective groundwater treatment and evidences that an adequately high nitrogen LR should be maintained to avoid the generation of excess sulfide.
Keywords: Autotrophic denitrification; Denitritation; Drinking water; Elemental sulfur; Nanofiltration; Packed bed reactor